Optimizing the anesthetic care of patients with aromatic l-amino acid decarboxylase deficiency - Kanjia, Megha K.; Jooste, Edmund H.; Illig, Melissa; Neifeld Capps, Jennifer; Eisner, Christoph; Fan, Shou Zen; Lenarczyk, Jerzy; Wojdacz, Rafał (Pediatric anesthesia, 2025)
Aromatic l-amino acid decarboxylase (AADC) deficiency is a rare autosomal recessive disorder that results in a lack of the monoamine neurotransmitters dopamine, serotonin, norepinephrine, and epinephrine. Patients present with a wide spectrum of symptoms, including motor and autonomic dysfunction, hypotonia, and developmental delay, often before the age of one. Until recently, treatment options were limited to symptom control, but the recent approval of the first gene therapy for AADC deficiency in Europe and the UK has provided an alternative to treating symptoms for this disease. Eladocagene exuparvovec is a one-time gene therapy, administered bilaterally to the putamen by magnetic resonance imaging-guided stereotactic neurosurgery. While administration of the gene therapy itself is minimally invasive, the anesthetic management of patients with AADC deficiency is challenging due to the absence of sympathetic regulation secondary to the lack of adrenergic neurotransmitters. Optimal anesthetic management requires an understanding of the complex and heterogeneous nature of the disease. Hemodynamic instability, temperature dysregulation, and hypoglycemia are of primary concern, but there are also challenges regarding intravenous access and airway management. A thorough preoperative assessment is essential and should be guided by the patient's history. Advanced planning is necessary regarding the timing of the procedure schedule and operative plan; meticulous preparation, simulation for the operating room, as well as communication with all perioperative staff members, are crucial. Intraoperatively, utmost care must be taken to protect the skin, maintain body temperature, and to prepare for inotropic and/or glycemic support as needed. Postoperative intensive care management is necessary for consideration of postoperative extubation and provision of supportive care. With careful planning, preparation, and vigilance, patients with AADC deficiency can safely undergo anesthesia.